Service user engagement in healthcare education as a mechanism for value based recruitment: An evaluation study. (January 2018) - Heaslip, Vanessa; Scammell, Janet; Mills, Anne; Spriggs, Ashley; Addis, Andrea; Bond, Mandy; Latchford, Carolyn; Warren, Angela; Borwell, Juliet; Tee, Stephen
Abstract: Aim: Within the United Kingdom (UK) there is an increasing focus on Values Based Recruitment (VBR) of staff working in the National Health Service (NHS) in response to public inquiries criticising the lack of person-centred care. All NHS employees are recruited on the basis of a prescribed set of values. This is extended to the recruitment of student healthcare professionals, yet there is little research of how to implement this. Involving Service Users in healthcare educational practice is gaining momentum internationally, yet involvement of service users in VBR of 'would be' healthcare professionals remains at an embryonic phase. Adult nurses represent the largest healthcare workforce in the UK, yet involvement of service users in their recruitment has received scant attention. This paper is an evaluation of the inclusion of service users in a VBR of 640 adult student nurses. Background Design: This study used a participatory mixed methods approach, with service users as co-researchers in the study. Methods: The study consisted of mixed methods design. Quantitative data via an online questionnaire to ascertain candidates' perspectives ( n = 269 response rate of 42%), and academic/clinical nurses ( n = 35 response rate 34.65%). Qualitative data were gathered using focus groups and one to one interviews with service users ( n = 9). Data analysis included descriptive statistics and thematic analysis. Findings: 4 overarching themes were identified; increasing sense of humanness, substantiating care values; impact of involvement; working together and making it work, a work in progress. Conclusion: The findings from the study highlight that involving service users in VBR of student healthcare professionals has benefits to candidates, service users and local health services. Appreciating the perceptions of healthcare professionals is fundamental in the UK and internationally to implementing service users' engagement in service enhancement and delivery. Findings from this study identify there may be a dissonance between the policy, the nurses' thoughts and their practice. Highlights: Involving service users in the interviewing of student nurses has multiple benefits. Service users ensure a focus on values in a value based recruitment process. Involving Service Users in the interviewing process provides a human dimension.